The impact of First-time Adoption of International Financial Reporting Standards in the value Relevance: applied research for a sample of banks listed in the Iraq Stock Exchange (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:             The research aims to evaluate the impact of the transition from local accounting standards to International Financial Reporting Standards (IFRS) on financial statements, and measure the change in the value relevance of financial accounting information, i.e. the book value of property rights and profits before and after applying the International Financial Reporting Standard (IFRS1), and to test the impact of applying the standard. In order to suit the book value per share and the value of accounting earnings per share, and for the purpose of achieving the research objective, financial statements were prepared for the banks in the research sample that applied the International Financial Reporting Standard (1) and were listed on the Iraq Stock Exchange for the period (2013-2015) before adoption and for the period (2016-2019) after. Adoption and then the value suitability was calculated through the use of the price model, enhanced with statistical methods and programs represented by the (SPSS) program to test the research hypotheses, and the most important conclusions reached are that the adoption of international accounting standards and international financial reporting standards affects the value suitability of the banks in the research sample and this It confirms the validity of the conclusion that financial statements prepared based on international financial reporting standards express themselves more appropriately than traditional statements, and the most important recommendations reached are that bank management must adhere to all requirements of international accounting and financial reporting standards to enhance the characteristics of accounting information for users of financial statements, because adherence to those standards It makes the financial statements honestly express the true contents of the numbers and events they contain.